2013
DOI: 10.5812/hepatmon.8611
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of Chronic Hepatitis C Evolution in HIV Co-Infected Patients From Romania

Abstract: BackgroundDue to a recent alarming increase in the number of HIV-HCV co-infected patients in Romania.ObjectivesA cross sectional study was conducted to assess the baseline predictors of liver disease evolution.Patients and Methods83 HIV-HCV co-infected patients, untreated for HCV infection, were evaluated for viral replication, liver fibrosis (estimated by a noninvasive marker - FIB4), and plasma levels of IP-10 (interferon-gamma inducible protein 10) - a cytokine associated with an unfavorable outcome of HCV … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 25 publications
0
2
1
Order By: Relevance
“…Also, the present study showed a lack of statistical correlation between HCV genotypes and other modes of transmission, the serum HCV-RNA concentration, CD4 level and antiretroviral treatment. In contrast with studies conducted by other authors 42 , 45 , 52 , a significant relation was established between HCV genotypes and HIV viral load, where it was observed that patients infected with HCV genotype 1 presented with detectable viral load were significantly higher than those with genotype 3 ratio. The maintenance of viral load to undetectable levels is achieved by regular and continuous use of antiretroviral therapy 24 .…”
Section: Discussioncontrasting
confidence: 97%
“…Also, the present study showed a lack of statistical correlation between HCV genotypes and other modes of transmission, the serum HCV-RNA concentration, CD4 level and antiretroviral treatment. In contrast with studies conducted by other authors 42 , 45 , 52 , a significant relation was established between HCV genotypes and HIV viral load, where it was observed that patients infected with HCV genotype 1 presented with detectable viral load were significantly higher than those with genotype 3 ratio. The maintenance of viral load to undetectable levels is achieved by regular and continuous use of antiretroviral therapy 24 .…”
Section: Discussioncontrasting
confidence: 97%
“…IP-10 is a CXC chemokine that binds to the CXCR3 immune system receptor present on a number of cells, including monocytes, NK cells and T cells. Various studies have identified elevated IP-10 levels as a negative prognostic indicator for both HCV infection and HIV infection, and it has also been proposed as a negative predictor of response to antiviral therapy in HCV mono-infected and HIV/HCV co-infected patients [ 108 , 109 ]. A high rate of inflammation, and subsequent activation of the endogenous IFN system, as well as significant levels of oxidative damage [ 110 ], have been proposed as mechanisms behind IP-10 elevation.…”
Section: Accelerated Liver Fibrosis In Human Immunodeficiency Virumentioning
confidence: 99%
“…The highest seroprevalence of HIV infection was observed in young persons (aged 20-39 years), whereas HBV and HCV infections were prevalent among elderly people (aged 50-59 years for HBV and more than 60 years for HCV). Our data suggest a high seroprevalence of unrecognized viral hepatitis infections in older people who were never screened and were exposed to potentially unsafe healthcare-associated parenteral practices before 1990-1995 ( 4 ). Although all the tested subjects received a 6-monthly retesting recommendation, retesting was performed for only 24% of the subjects; 0.2% of them were newly diagnosed with HIV (14 patients), 0.3% were diagnosed with HBV (19 patients), and 0.8% were diagnosed with HCV (52 patients).…”
mentioning
confidence: 84%